A quadruple cascade protocol for the one-pot synthesis of fully-substituted hexahydroisoindolinones from simple substrates - Zhang, Hong-Bo; Luo, Yong-Chun; Hu, Xiu-Qin; Liang, Yong-Min; Xu, Peng-Fei (Beilstein Journal of Organic Chemistry, 2016)
A new and efficient synthetic method to obtain fully-substituted hexahydroisoindolinones was developed by using bifunctional tertiary amine-thioureas as powerful catalysts. As far as we know, there is no efficient synthetic method developed toward fully-substituted hexahydroisoindolinones. The products were obtained in good yield and diastereoselectivity. The one-pot cascade quadruple protocol features readily available starting materials, simple manipulation, mild conditions and good atom economy.
Keywords: bifunctional catalysis; hexahydroisoindolinones; one-pot synthesis; quadruple cascade